Shot-earth for sustainable constructions. (10th April 2020) - Curto, A.; Lanzoni, L.; Tarantino, A.M.; Viviani, M.
Highlights: A study about the shot-earth as building material is proposed. The working principle of the shotcrete is here extended to rammed earth. The shot-earth is based on soil coming from excavation in construction sites. An experimental campaign has been carried out to assess the mechanical performance of shot-earth. It is shown that shot-earth resembles a low strength concrete. Abstract: Earth has been used worldwide as a building material for centuries and it is still one of the most used construction materials. In many countries the excavated soil is becoming one of the largest construction waste and its disposal is costly and problematic. For this reason, there is a rising interest in employing the excavated soil directly in field, possibly as an added value construction material. In this paper a new type of rammed earth is presented. This new material is based on the shotcrete technology and has been named shot-earth. A mix of stabilized soil, aggregates and water is consolidated by high speed projection rather than by mechanical compaction to obtain both structural and non-structural elements. The first characterization of the physical properties of this material has shown the great potential of this technology.